Creativity-Relevant Personal Characteristics among Indonesia Creative Workers - Nugroho J. Setiadi; Rudy Aryanto (The Winners, 2014)
The study aims to identify Creativity-relevant Personal Characteristics among creative workers in Indonesia’s creative industry. Identification of the constituent elements of the nature of the changes needs to be measured. Researchers have advocated replacing creativity-relevant personal characteristics based on the five-factor model to investigate how individual differences stimulate creativity. This study presents data supporting reliability (internal consistency) and validity (criterion and construct) of the instrument. Validity of the instrument is based on the content validity involving art and design experts. The 220 creative workers from several creative industry firms in Indonesia participated as samples in this research. Results of a factor analysis indicated a five factor solution of creative characteristics and behavior. Discussion of findings and the most important ways in which individuals differ in their enduring emotional, interpersonal, experiential, attitudinal, and motivational styles for stimulating creativity are presented.